Investigating the relationship between spiritual intelligence and resilience in infertile couples in Isfahan: A cross-sectional study - Masoume Pirhadi; Fatemeh Torabi; Fatemeh Mokhtari (Wolters Kluwer Medknow Publications, 2023)
Background: Infertility is a psychological crisis for a couple, spouse, and their families. Due to the positive effects of spiritual intelligence on the positive adaptation and growth of the individual under difficult circumstances, this study was conducted to determine the relationship between spiritual intelligence and resilience in infertile couples in Isfahan. Materials and Methods: This cross-sectional study was performed in 2020 on 162 infertile couples. Data were collected by the convenience sampling method from infertile couples referring to Infertility Centers in Isfahan through two standard questionnaires. Data analysis was performed using descriptive statistical methods for quantitative variables. The relationship between spiritual intelligence and resilience score was investigated using inferential statistical methods of Pearson's correlation coefficient and multiple linear regression. A p value of less than 0.05 was considered significant. Results: The results showed that the mean age Standard Deviation (SD) of women and their spouses was 32.01 (5.86) and 36.30 (5.82) years, respectively. Pearson's correlation coefficient showed that there was a significant positive direct relationship between resilience score with total spiritual intelligence score (r = 0.36, p < 0.001) and its dimensions Critical Existential Thinking (CET) (r = 0.60, p < 0.001), personal meaning production (PMP) (r = 0.38, p < 0.001), Transcendental Awareness (TA) (r = 0.43, p < 0.001), and Conscious State Expansion (CSE) (r = 0.53, p < 0.001). The PMP (t = 6.38, p < 0.001) and the CSE (t = 2.15, p = 0.03) were significant predictors of resilience scores. Conclusions: The result of our study showed that couples with a higher level of spiritual intelligence had a better understanding of the problems and harms of primary infertility and would cope with it more efficiently.